Assessment of Land Use Pattern and Landscape Ecological Risk in the Chengdu-Chongqing Economic Circle, Southwestern China - Chunfen Zeng; Jun He; Qingqing He; Yuqing Mao; Boya Yu (Land, 2022)
The Chengdu-Chongqing Economic Circle (CCEC) is becoming the fourth growth pole in China after the Yangtze River Delta Economic Circle (YRDEC); Guangdong, Hong Kong, and Macao Economic Circle (GBAEC); Beijing, Tianjin, and Hebei Economic Circle (BTHEC). The land use and landscape ecological management of the CCEC is critical to its social and economic development. Using ArcGIS modeling and Fragstats processing methods, we divided the CCEC into 5 km × 5 km ecological risk areas and constructed a landscape ecological risk index evaluation model to calculate the spatial and temporal dynamic changes in the urban expansion and landscape ecological risk over the last 20 years. The results show that the land use was mainly cultivated land, which exhibited a decreasing trend and was mainly converted to construction land and forest land. The change in the construction land exhibited a continuous expansion trend with the dual core in Chengdu-Chongqing. The average risk of 10,155 risk communities was about 0.16. The expansion of human activities increased the landscape ecological risk of the construction land, and the risk of the edge of the cultivated land was higher than the internal risk value. The ecological risk index values of 16 cities in the study area ranged from 0.02 to 0.28. The resistance of the landscape pattern to external disturbance was stronger than that in other regions of China. The landscape ecological risk is controllable overall. However, the higher level of economic development in Chengdu, Chongqing, and other mature cities poses a greater landscape ecological risk. The results of this research provide an important reference for promoting the optimization and construction of the land space in the CCEC, building ecological shelters, and preventing ecological risk in the upper reaches of the Yangtze River.